Comparison of different imaging devices and navigation systems for cervical pedicle screw placement: an experimental study on screw accuracy, screw placement time and radiation dose - Mandelka, Leon Eric; Wolf, Justine; Medrow, Antonia; Grützner, Paul Alfred; Vetter, Sven Y.; Gierse, Jula (Scientific reports, 2024)
Cervical pedicle screws (CPS) provide biomechanically superior fixation compared to other techniques but are technically more demanding. Navigated CPS placement has been increasingly reported as a safe and accurate technique, yet there are few studies comparing different combinations of imaging and navigation systems under comparable conditions. With this study, we aimed to compare different imaging and navigation systems for CPS placement in terms of accuracy, screw placement time and applied radiation dose. For this experimental study, navigated CPS placement was performed at levels C2 to C7 in 24 identical radiopaque artificial spine models by two surgeons with different levels of experience using three different combinations of intraoperative 3D imaging devices and navigation systems. Accuracy, time and radiation dose were compared between the groups. In total, 288 screws were placed. Accuracy was > 98% in all groups with no significant differences between groups or between surgeons (P = 0.30 and P = 0.31, respectively), but the inexperienced surgeon required significantly more time (P < 0.001). Radiation dose was significantly higher with iCT compared to CBCT (P < 0.0001). Under experimental conditions, accuracy rates of > 98% were achieved for navigated CPS placement regardless of the imaging modality or navigation system used. Radiation doses were significantly lower for CBCT compared to iCT guidance.